Higher Undercarboxylated to Total Osteocalcin Ratio Is Associated With Reduced Physical Function and Increased 15‐Year Falls‐Related Hospitalizations: The Perth Longitudinal Study of Aging Women. (3rd December 2020) - Smith, Cassandra; Lewis, Joshua R; Sim, Marc; Lim, Wai H; Lim, Ee Mun; Blekkenhorst, Lauren C; Brennan‐Speranza, Tara C; Adams, Leon; Byrnes, Elizabeth; Duque, Gustavo; Levinger, Itamar; Prince, Richard L
ABSTRACT: Evidence from animal models suggests that undercarboxylated osteocalcin (ucOC) is involved in muscle mass maintenance and strength. In humans, the ucOC to total (t)OC ratio may be related to muscle strength and perhaps physical function and falls risk, but data are limited. We tested the hypothesis that ucOC and ucOC/tOC ratio are associated with muscle function (muscle strength and physical function) in older women and 15‐year falls‐related hospitalizations. Serum tOC and ucOC were assessed in 1261 older women (mean age 75.2 ± 2.7 years) forming the Perth Longitudinal Study of Aging Women (1998 to 2013). Timed‐up‐and‐go (TUG) and grip strength were assessed at baseline and at 5 years. Falls‐related hospitalizations (14.5‐year follow‐up) were captured by the Hospital Morbidity Data Collection, via the Western Australian Data Linkage System. At baseline, women with higher ucOC/tOC ratio (quartile 4) had slower TUG performance compared with quartile 1 (~0.68 seconds, p  < .01). Grip strength and 5‐year change of TUG and grip were not different ( p  > .05) between quartiles. Fear of falling limiting house, outdoor, and combined activities was significantly different across quartiles ( p  < .05). Higher ucOC/tOC was significantly associated with poorer TUG performance at baseline and 5‐year change in performance, increased walking aid use, and fear of falling (all p  < .05). Higher ucOC was related to lower grip strength at baseline ( p  < .05) but not 5‐year change in strength. Those with the highest ucOC/tOC had greater falls‐related hospitalizations (unadjusted log rank, p = .004) remaining significant after adjusting for key variables (hazard ratio [HR] = 1.31, 95% confidence interval [CI] 1.09–1.57, p = .004). We identified a large proportion of older women with high ucOC/tOC ratio who had reduced physical function, including its long‐term decline and increased risk of falls‐related hospitalizations. Early identification of women at higher risk can enable prevention and intervention strategies to occur, reducing risk for injurious falls. © 2020 American Society for Bone and Mineral Research (ASBMR)..